Analysis of Basal Plane Dislocation Dynamics in PVT-Grown 4H-SiC Crystals during High Temperature Treatment. (3rd July 2019) - Raghothamachar, Balaji; Yang, Yu; Guo, Jianqiu; Dudley, Michael
Abstract : Fundamental understanding of the generation and multiplication of basal plane dislocations (BPDs) in PVT-grown 4H-SiC crystals is critical for design of growth strategies to control their densities during PVT growth of 4H-SiC crystals. Direct observation of thermal gradient induced motion of basal plane dislocations by in-situ synchrotron X-ray topography imaging of PVT-grown 4H-SiC wafers subject to high temperature treatment has provided an opportunity to analyze the movement of dislocations. Dislocations with Burgers vector along the off-cut [11-20] direction were found to be the only dislocations involved in deformation during heat treatment and the segments of dislocations used for velocity measurements were found to be either pure screw comprised of both Si- and C- core partials or 60° dislocations comprised of purely Si cores. Using the kink-diffusion model, the activation energies for dislocation motion have been estimated from the velocity data for each of these dislocation types and found to be 2.21 eV for 60° and 3.28 eV for pure screw segments, respectively. These values are in good agreement with the macroscopic studies of yielding of semiconductor crystals during high temperature compression and indentation experiments. Quantitative expression of the temperature dependent critical resolved shear stress required for dislocation motion has been derived from this analysis.